HAKIKAT FONOLOGI DALAM KAJIAN LINGUISTIK - Muhammad Fadhil Uzmi; Aprilla Nurul (Yayasan Haiah Nusratul Islam, 2024)
Phonology is a branch of linguistics that studies the sounds of language, and the processes of their formation and change. The smallest unit of language that functions, the term phoneme has the ability to distinguish meaning. Phonemes differ based on where they are in the word, such as the first phoneme in the word